Future role of agriculture in multifunctional development of rural areas - Runowski, Henryk; Zietara, Wojciech (Applied Studies in Agribusiness and Commerce, 2010)
In the paper the changes in agriculture in terms of falling share of agriculture in gross domestic product and decrease in the share of persons employed in agriculture in total employment in Poland and selected countries are discussed.The main driver of these changes is a faster pace of development of non-agricultural activities and continually deteriorating relations between the costs of production factors and prices of agricultural products. The rate of growth in labor costs and prices of the means of production for agriculture is much faster than the rate of increase in prices of agricultural products. This causes the decline in profitability of agricultural production which in creases the size of farms. The pace is dependent on the level of economic development of the country. The study also identified trends in the structure of farms, functions and systems of agriculture in the generational perspective.The polarization of the farms will deepen.A strong group of commodity farms and a group of so-called self – subsistence social farms will emerge. Agriculture in Poland will have a dual nature. In addition to the production function and social services agriculture will expand the scope of service functions for the environment and society.